Association of Active Surveillance and Decolonization Program on Incidence of Clinical Cultures Growing Staphylococcus aureus in the Neonatal Intensive Care Unit. (4th October 2017) - Voskertchian, Annie; Akinboyo, Ibukunoluwa; Sick, Anna; Aucott, Susan W; Milstone, Aaron M
Abstract: Background: Staphylococcus aureus (S. aureus) is a common cause of neonatal infections. Our aim was to determine sustainability of a program of active surveillance cultures and decolonization on the incidence of positive S. aureus clinical cultures. Methods: We performed a retrospective cohort study of neonates admitted to a tertiary NICU from April 1, 2011 to June 30, 2016. We compared the incidence of S. aureus -positive clinical cultures before and after implementation of the program. S. aureus -positive cultures were defined as non-surveillance cultures that grew S. aureus . Cultures of specimens were considered unique events if collected from the same body site at least 30 days apart or from different body sites at least 14 days apart. Hospital-onset was defined as clinical culture growth obtained more than two days after admission. Hospital-onset cultures were used as comparison, as cultures obtained in the first 48 hours should not be affected by the program and the effect may be more pronounced. We used 2-sided Poisson tests for comparing independent incidence rates and interrupted time series analysis. Results: There were 70 and 72 positive cultures in the pre (29, 220 patient-days) and post (47, 135 patient-days) intervention periods, respectively. Overall, there was a 36% reduction in the incident rate of S. aureus -positive cultures (IRR= 0.64, 95% CI 0.460-.884). Prior to the intervention, the quarterly rate of positive cultures did not change over time (Figure 1a). After implementation, there was a non-significant immediate 24.1% reduction in S. aureus cultures (IRR=0.76, 95% CI 0.35–1.65), after which positive cultures decrease by 4.1% per quarter (IRR=0.959, 95% CI 0.93–0.99). When examining the hospital-onset cultures, there was a 43% decrease, when comparing the two periods (IRR=0.57 95% CI 0.411- 0.801). After implementation of the program, there was a similar immediate non-significant decrease of hospital-onset S. aureus cultures of 37.9% (IRR=0.621, CI 0.24–1.58), and a non-significant 3.0% per quarter decrease in hospital-onset positive cultures (Figure 1b) (IRR=0.97, CI 0.92–1.023). Conclusion: Active surveillance and decolonization may effectively and sustainably decrease S. aureus- positive clinical cultures in the NICU. Disclosures: All authors: No reported disclosures.